Effect of Locus of Control, Organization of Citizenship Behavior and Work Achievement on Employee Performance (Study at: Palopo City Environmental Service) - Ilham Tahier; Andi Nadirah; Akmal Bakti (Institute of Computer Science (IOCS), 2022)
This study aims to examine the effect of locus of control, organizational citizenship behavior and work performance on employee performance. The population in this study were all employees at the Environmental Service of Palopo City, amounting to 869 employees, while the sample in this study was part of the total population with the determination of the sample using the Slovin formula so that a sample of 90 employees was obtained. The data collection technique in this study used a questionnaire with a Likert scale of 1 – 5. The data were analyzed with the help of SPSS 21 Statistical Software . The results obtained from partial statistical testing showed that locus of control and work performance had no effect on employee performance. Meanwhile , organizational citizenship behavior has a positive effect on employee performance. Which means that the greater the influence of organization citizenship behavior , the better the performance of employees at the environmental service of the city of Paopo.